(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
The author of this paper is trying to give answers to some questions. First, is the European cultural identity after which we are searching for now similar or close to the ethnic or national identity and how it shows itself historically in modern national states and can the model of the European citizen be derived from the model of nationality, according to the example how they are derived in Europe today. Second, that the European identity can be anticipated similar to the classic search for the identity, that it is a question of primordial identity, but yet it is a matter of something that there is no clearly determined borders, and which forms and changes permanently: simply “a cultural war” is waging about the question how to define, practice and simply imagine the identity. Finally, the discourse for the European cultural identity implicate very clear relation between the identity and culture, by the reasons that the base of the national identity is in the culture, it is a general media, bloodstream where members of a community live in. Simply the people should learn to live in plural cultural communities. In that sense Europe might start to build itself as a community of different cultures.